Study of dielectric and magnetic properties of CaCu3Ti4-XMnXO12 (X = 0 and 0.1) ceramic synthesized through semi-wet route - Kumar V.; Pandey S.; Verma M.K.; Singh S.; Rai V.S.; Prajapati D.; Singh N.B.; Prajapat C.L.; Gangwar A.; Mandal K.D. (My University, 2025)
This communication recognized the effect of Mn-doped as well as non-doped CCTO ceramic with the help of thermogravimetric analysis (TGA), Fourier transform infrared (FT-IR) spectroscopy, X-ray diffraction (XRD), high-resolution scanning electron microscopy (HR-SEM), high-resolution transmission electron microscopy (HR-TEM) MPMS, and dielectric studies, respectively. The thermal behavior of CCTO and CCTMO ceramics was studied by TGA. The metal–oxygen bond was analyzed by FT-IR spectroscopy. The phase formation of CCTO and CCTMO ceramics was analyzed by X-ray diffraction pattern. In the CCTO ceramic, there is a minor phase TiO2 peak also recorded. The microstructure studies of CCTO and CCTMO were examined by HR-SEM and HR-TEM. The metal ions were recorded in their required stoichiometric ratio, examined by EDX. Magnetization vs. field up to ± 2 T was carried out using a superconducting quantum interference device (MPMS-XL, Quantum Design). The maximum dielectric constant of CCTMO ceramic was measured 500 at 308 K and the minimum tangent was recorded 0.8 at 100-Hz frequency. © 2022, The Author(s) under exclusive licence to Australian Ceramic Society.